Accurate Low-Current Measurement Circuit for Multimeters and Oscillograps - Shuqin Geng; Chen Liu; Jinhui Wang; Ligang Hou; Ying Yuan (Institute of Advanced Engineering and Science, 2014)
A simple and high-precision current-to-voltage (I/V) converter circuit for multimeters and oscillographs is presented in this paper. The I/V converter measures the electric current with uA and nA selectable ranges in the frequency range from direct current to 1 MHz. Circuit technology is also discussed. System Architecture is presented and dual polarity power is designed. Power detector circuit is explained. Measurement data are obtained. Linearity and the error are analyzed. The typical accuracy of the μCurrent is higher by 0.085% in the μA and nA ranges. μCurrent can be used in detecting low uA and nA in current systems, chips, and modules. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5004